(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
In light of the development of the business environment and expansion of economic entities for staying in labor market, this led to the development of audit processes and the emergence of new concepts, perhaps the most important is audit quality to provide an appropriate assurance about the integrity of the financial statements. Therefore, the auditor seeks to evaluate evidence to suit the modern understanding of auditing in order to enhance his technical opinion. The aim of the research is to explore the relationship of audit evadence, to the quality of audit and to reflect it on the evidence. The research is based on the premise: "Given the evolution of the nature and size of the activities of the economic units, and the emergence of audit quality concept, these factors affect the evaluation of evidence required to support the auditor’s opinion on the validity of the financial statements." The research leads to a set of conclusions that can be summarized as follows: (1) The services provided by the auditor are to be satisfied by collecting evidence consistent with the recent trends of auditing.( 2) Audit evidence gives a high level of confidence in the validity of the information contained in the financial statements. (3)Related management assertions associated with financial statements, strong evidence and quality. Because they can be relied on by the auditor when expressing his opinion.